Model of functioning of professional qualities of future navigators in the process of special training - Hlikman, Svitlana (ScienceRise: Pedagogical Education, 2018)
The article theoretically grounds the model of formation of professional qualities of future navigators in the process of professional training, presented by the purpose, theoretical-methodological, content-procedural and diagnostic blocks that distinctly reflect the directionality of the process of formation of professional qualities from the set aim till the final result. There are elucidated the destinations of separated elements (aim, tasks, principles, approaches, content of disciplines, forms methods and means of teaching, criteria, levels and results) in achieving the expected result. The purpose block of the model provides determining aims and tasks of the process of formation of professional qualities of future navigators. The theoretical-methodological base of the process of formation of professional qualities are principles and approaches (competence, synergetic, system, axiological, activity, resource). The content-procedural block of the model includes a series of disciplines of the cycle of professional and practical training, which learning favors the formation of professional qualities of future navigators, covers forms, methods and means of teaching. The assessing-resulting block of the model determines criteria (motivational, cognitive, activity-behavior, reflexive), correspondent indicators, formation levels of professional qualities (low, middle, high). In particular, this bock includes the result of the process (formation of professional qualities of future navigators), coordinated with the initial aim. There are indicated the pedagogical conditions, necessary for realizing the developed model, namely: 1) provision of the positive motivation of future navigators for formation of professional qualities in the process of learning disciplines of the cycle of professional and practical training; 2) orientation of the content of disciplines of the cycle of professional and practical training on the formation of professional qualities of future navigators; 3) provision of active repetitions of professional situations in the process of learning disciplines of the cycle of professional and practical training